Intelligent agent server (NetInt)system - David A. Karapetyan (Изд-во НАН РА)
The paper describes Intelligent Agent Server system, which employs software agents. A detailed description of software agents as well some examples of the system application, particularly intrusion detection in local networks is given.
Keywords: Mathematics; Computer software